The impact of stressful life events on antiretroviral treatment adherence and viral load amongst adults in Gugulethu, Cape Town - Coombs, Julie-Anne (Department of Paediatrics and Child Health, 2021)
Optimal antiretroviral treatment (ART) adherence is critical in achieving virologic suppression. Most people living with HIV (PLWH) experience HIV-related challenges which may be compounded by the experience of stressful life events (SLE) with adverse effects on their ART adherence and therefore affecting viral suppression. The highest concentration of people living with HIV (PLWH) is in low-and-middle income countries (LMIC) which are challenged with high rates of poverty and unemployment. Limited published data is available on the impact of the stressful life events experienced by PLWH in LMIC on ART adherence and viral load. A secondary analysis was conducted using data collected in a randomised control trial (RCT) which investigated the impact of a real-time electronic adherence monitoring device (EAMD) on ART adherence in ART-naïve individuals to assess the impact of SLE on ART adherence and viral load. Part A of this dissertation includes the study proposal/ protocol as approved by the Departmental Research Committee and the Human Research Committee at the University of Cape Town. Part B details the literature review which examined all published studies which report on stressful life events in PLWH, with ART adherence or a viral load as an outcome. The review included published literature from 2008 to 2019. Part C includes the publish-ready manuscript which details the statistical analysis, results and interpretation of the secondary analysis of impact of SLEs on ART adherence and viral load among 200 individuals living with HIV. Part D, appendices were included as supporting documentation necessary for the conduct of this research and as required for the completion of this dissertation. The American Psychological Association (APA) 6th Edition referencing style was used for Part A and B. The Vancouver referencing style was used for Part C as per the instructions for authors by the Aids and Behaviour journal guidelines.